Accumulation differences of high-value ingredients in different phenotype Lonicera macranthoides: insights from integrative metabolome and transcriptome analyses - Zeng, Juan; Long, Yu Qing; Zhu, Jia Yuan; Fu, Xue Sen; Zhang, Jing Yu; He, Jia Wei; Liu, Xiao Rong; Wang, Zhi Hui; Tong, Qiao Zhen; Liu, Xiang Dan; Zhou, Ri Bao (Frontiers in Plant Science, 2025)
BackgroundLonicera macranthoides Hand.-Mazz., the primary sources of Lonicerae Flos(Shanyinhua), brings great medicinal and economic value as an invaluable source of natural bioactive compounds. Nutrient and metabolites accumulation generally changed accompany with its floral development and opening. While the specific accumulation pattern and the underlying molecular regulatory networks remain unclear. MethodsThe present study intergrated a comparative analysis upon UPLC-MS/MS-based metabolomics and RNA-seq-based transcriptomics to revealed the differences in accumulation of flavonoids, phenolic acids, and terpenoids between the xianglei-type (corolla-closed) and wild-type (corolla-unfolded) of L. macranthoides flowers. Results and conclusion674 differentially accumulated metabolites(DAMs) were identified in WT and XL, with 5,776 common differentially expressed genes(DEGs), revealing a significant differences in accumulation of flavonoids, phenolic acids, and terpenoids during the late stage of flower development between the xianglei-type and wild-type of L. macranthoides flowers. Combined analysis further identified 36 hub genes, major transcription factors and hormone-related genes, which play key roles in the differential accumulation of the abovementioned metabolites. These lines of evidences provide a molecular basis for the metabolic changes occurring during growth and can be significantly implicated in further research on the biosynthetic pathways associated with high-value potent active components in woody plants.